Law Enforcement Against Violation of Overstaying Perpetrated by Foreigners: A Study in Class I Immigration Office of Ternate - Tussabah, Aisha; Abdulajid, Syawal; Rumkel, Nam (Dinasti Research, 2025)
The title of this research is “Law Enforcement Against Violation of Overstaying Perpetrated by Foreigners: A Study in Class I Immigration Office of Ternate.” The object of this study is the law enforcement carried out against violations of residence permits by foreign. The objective is to analyze the law enforcement carried out against violations of residence permits by foreigners (overstay) in the working area of the Class I Ternate Immigration Office? This paper employed the juridical-empirical approach. This was qualitative field research because the primary data was collected directly from respondents through interviews and documentation. Results show that law enforcement against violations of residence permits by foreigners in the working area of the Class I Immigration Checkpoint of the Ternate Immigration Office has basically been implemented in accordance with the provisions stipulated in Law Number 6 of 2011 concerning Immigration, especially Article 75 and Article 78. The enforcement is more dominantly administrative in nature through the implementation of immigration administrative actions, such as deportation and deterrence, which are considered as a form of fast and efficient non-litigative action. From 2021 to mid-2025, 58 administrative actions were recorded, with the highest number of deportations occurring in 2023.